2022
DOI: 10.1007/s42107-022-00500-5
|View full text |Cite
|
Sign up to set email alerts
|

Developing sustainability assessment indicators for measuring contractor’s performance during the construction phase of construction projects in Jordan

Abstract: The development of sustainability assessment indicators has become a hot topic globally, while sustainability practices are uncontrollably growing in the construction industry. However, the construction industry itself has negative impacts on the environment, society, and the economy. Therefore, during the construction phase, the contractors who are responsible for delivering construction projects should have a suitably adaptable sustainability solution. Qualified and experienced contractors are, of course, vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Adopting GHRM strategies and enhancing technical innovations can contribute to improving sustainability and economic performance. 2019); Chiappetta Jabbour and Sousa Jabbour (2016) that discuss the intersection of GHRM and GSCM [7,12,17,24,26,27].…”
Section: Highlighting the Importance Of Sustainable Human Resource Ma...mentioning
confidence: 99%
See 1 more Smart Citation
“…Adopting GHRM strategies and enhancing technical innovations can contribute to improving sustainability and economic performance. 2019); Chiappetta Jabbour and Sousa Jabbour (2016) that discuss the intersection of GHRM and GSCM [7,12,17,24,26,27].…”
Section: Highlighting the Importance Of Sustainable Human Resource Ma...mentioning
confidence: 99%
“…Several authors have developed different approaches to categorize GHRM practices. For example, ˙Iktisadi Ve et al [21] identified four GHRM practices: green employee acquisition, green employee appraisal, and green employee rewards; Luay Jum'a [25] proposed a unidimensional measure for GHRM; Alnsour, Moawiah [26] examined green hiring, green training and involvement, and green performance management and compensation; Kara, Karahan, and Edinsel, Sercan [10] studied green recruitment, green rewards and compensation, and environmental training; Tang et al Alnsour, Moawiah [27] proposed five GHRM practices: green recruitment and selection, green training, green performance management, green pay and reward, and green involvement. Nawangsari and Sutawidjaya [28] suggested the following practices: green recruitment, green performance management, green training and development, green compensation, and green employee relations.…”
Section: Green Human Resource Managementmentioning
confidence: 99%
“…Although its increase in popularity, there is no consensus regarding GHRM practices [24]. Several authors developed different approaches; for instance, İktisadi Ve , et al [21] identified four GHRM practices: green employee acquisition, green employee appraisal, green employee rewards; Luay Jum'a [25] proposed a unidimensional measure for GHRM; Alnsour, Moawiah [26] examined green hiring, green training and involvement and green performance management and compensation; Kara, Karahan & Edinsel, Sercan [10] studied green recruitment, green rewards and compensation and environmental training; Tang et al Alnsour, Moawiah [27] proposed five GHRM practices: green recruitment and selection, green training, green performance management, green pay and reward and green involvement. Nawangsari and Sutawidjaya [28] suggested the following practices green recruitment, green performance management, green training and development, green compensation, and green employee relations.…”
Section: Green Human Resource Managementmentioning
confidence: 99%
“…Another reason might be the cost deviation of construction projects [19]. The contractors should be selected based on their performance in previous projects [20][21][22][23]. Previous studies showed that there is a lack of measurement tools for assessing the performance of contractors in construction projects.…”
Section: Introductionmentioning
confidence: 99%